Simulation on the Breakthrough Curve During CO2 Adsorption from Biogas in a Fixed Bed Column - Kindi, Hablinur al; Tambunan, Armansyah Halomoan; Hartulistiyoso, Edy; Salundik, Salundik; Sutoyo, Edi; Sutisna, Setya Permana (ASEAN Journal of Chemical Engineering, 2023)
Separation of CO2 gas from the biogas can be accomplished by adsorption process. An adsorbent has a maximum capacity, so the adsorbent will eventually be saturated at a certain time. Therefore, it is necessary to simulate the adsorption mass transfer to produce a breakthrough curve. The breakthrough curve from the simulation of adsorption mass transfer was validated with the experimental data. The research was conducted using variations in temperature and pressure. The mass transfer simulation was solved using the finite difference method. The adsorbent used in this research was 13X zeolite and the biogas was obtained from cow dung waste. Convergent curves can be obtained in numerical simulations as breakthrough curves. This research shows that adsorption should occur at low temperatures and high pressure. Column height and flow velocity also influence the breakthrough time. The comparison of the simulated breakthrough time with experimental data is not much different with R2 0.9969. The striking difference is in the adsorption zone with average relative error (ARE) values ranging from 9.57% to 20.49%. From the results of entropy, enthalpy, and Gibbs free energy calculations, the biogas adsorption research on the 13x zeolite column is an exothermic and spontaneous process